Learning Design Repositories:Adapting Learning Design Specifications For Shared Instructional Knowledge - Dawn C. Buzza; David Bean; Kevin Harrigan; Tom Carey (The Canadian Network for Innovation in Education (CNIE), 2004)
The IMS Learning Design specification provides a potential means for capturing units of instruction in a machine-readable, consistent way. However, in order for the IMS Learning Design specification to be used widely by educators and instructional designers for whom it is intended, we will need effective ways for users to contribute to, access and adapt the repositories where reusable learning designs are collected and stored. This paper describes a project conducted to develop and test a prototype search model for learning design repositories. We argue for development of a controlled vocabulary to describe and label learning designs. In this way, designs can be accessed according to a variety of pedagogical, as well as topical criteria specific to the instructional purposes and perspectives of the user.